Online banking services in Morocco : the explaining factors - BENDOU , Najlae; YOUSSEF , Said (African Scientific Journal, 2024)
Abstract The aim of this paper is to understand the barriers to customer adoption of online banking in Morocco. We use qualitative analysis to comprehend the reasons that discourage the use of online banking in Morocco. We conducted semi-structured interviews. We use a sample of ten Moroccan bank executives. We provide strategic perspectives on the evolution of online banking. The results were analyzed using MAXQDA 22. The factors influencing the adoption of online banking are perceived ease of use, perceived usefulness, attitudes towards online banking, trust, service quality and perceived risk. In order to promote the use of online banking in Morocco, marketing campaigns need to focus on ease of use, perceived usefulness, as well as service quality, while addressing risk concerns. Keywords Ease of use, Intention to use, Online banking, perceived usefulness